An Integrated Full-bridge Class-DE Ultrasound Transducer Driver for HIFU Applications - Song, Ruiqi (My University, 2016)
This thesis present a CMOS integrated transducer driver for high intensity focused ultrasound (HIFU) applications. Because this driver will be used in a magnetic resonance imaging (MRI) environment, no magnetic components such as inductors and transformers have been used in this design. The transducer is directly connected to the driver without a matching network. The output stage of this driver is a full-bridge Class DE RF amplifer which is able to deliver more power than the previous design that has a half-bridge Class DE amplifer. The driver was also designed to be used in a transducer array. A digital control unit was integrated with the power amplifer that allows to program the drivers phase shift and duty ratio. A strategy to drive a ultrasound transducer array using the designed driver is also presented in this thesis. This design was implemented using the AMS H35B4 CMOS technology using the Cadence suite of design tools and occupies a die area of 2mm by 1.5mm with 20 input and output pads. Simulation and initial experimental results are presented in this work. The proposed integrated CMOS driver has an efficiency of 89.4% with 3.60 W of output power. Results are little bit different for each transducer.
Keywords: High intensity focused ultrasound; CMOS integrated transducer driver; Ultrasound transducer; Transducer array; Ultrasonic transducer driver design